2011
DOI: 10.1210/en.2010-1385
|View full text |Cite
|
Sign up to set email alerts
|

Organ-Specific Defects in Insulin-Like Growth Factor and Insulin Receptor Signaling in Late Gestational Asymmetric Intrauterine Growth Restriction in Cited1 Mutant Mice

Abstract: Late gestational placental insufficiency resulting in asymmetric intrauterine organ growth restriction (IUGR) is associated with an increased incidence of diabetes, cardiovascular and renal disease in adults. The molecular mechanisms mediating these defects are poorly understood. To explore this, we investigated the mechanisms leading to IUGR in Cited1 knockout mice, a genetic model of late gestational placental insufficiency. We show that loss of placental Cited1 leads to asymmetric IUGR with decreased liver,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…There was no change in the expression and phosphorylation level of IR, in line with the observations in asymmetric IUGR fetal brain in Cited1 mutant mice. (33) The results also indicated that maternal protein-restriction caused the reduced expression of SUR1 in the fetal hypothalamus. In SUR1 null mice, insulin’s ability to suppress hepatic gluconeogenesis was impaired.…”
Section: Discussionmentioning
confidence: 78%
“…There was no change in the expression and phosphorylation level of IR, in line with the observations in asymmetric IUGR fetal brain in Cited1 mutant mice. (33) The results also indicated that maternal protein-restriction caused the reduced expression of SUR1 in the fetal hypothalamus. In SUR1 null mice, insulin’s ability to suppress hepatic gluconeogenesis was impaired.…”
Section: Discussionmentioning
confidence: 78%
“…Vascularisation of the labyrinth was defective, with increased sinusoidal spaces resulting in a reduced surface area for nutrient transport (Rodriguez et al 2004). Consistent with placental insufficiency, mutant embryos were asymmetrically growth restricted during late gestation, with the majority of mutants dying in the neonatal period and survivors exhibiting catch-up growth within 8 weeks of birth (Rodriguez et al 2004, Novitskaya et al 2011.…”
Section: X-linked Genesmentioning
confidence: 99%
“…Cited1 knockout mice have growth restriction, late placental insufficiency and abnormalities in nephron patterning and pubertal mammary ductal morphogenesis (Howlin et al, 2006; Novitskaya et al, 2011; Plisov, 2005; Rodriguez et al, 2004). Although Cited1 was identified as a target of Sry in one mouse ChIP-CHIP study (Li et al, 2014), little is known about Cited1 in mouse testis.…”
Section: Discussionmentioning
confidence: 99%